Impact of postoperative dexmedetomidine infusion on incidence of delirium in elderly patients undergoing major elective noncardiac surgery: a randomized clinical trial - Sun Y; Jiang M; Ji Y; Sun Y; Liu Y; Shen W (Dove Medical Press, 2019)
Yuanyuan Sun,* Mingming Jiang,* Yunjing Ji, Yue Sun, Yao Liu, Wen ShenDepartment of Anesthesiology, Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of ChinaCorrespondence: Wen ShenDepartment of Anesthesiology, Affiliated Hospital of Xuzhou Medical University, No. 99 Huaihai West Road, Xuzhou, Jiangsu, People’s Republic of ChinaTel +86 05 160 850 2043Email shenwen8694@163.com*These authors contributed equally to this workPurpose: Postoperative delirium is a serious and common complication, it occurs in 13–50% of elderly patients after major surgery, and presages adverse outcomes. Emerging literature suggests that dexmedetomidine sedation in critical care units (intensive care unit) is associated with reduced incidence of delirium. However, few studies have investigated whether postoperative continuous infusion of dexmedetomidine could safely decrease the incidence of delirium in elderly patients admitted to general surgical wards after noncardiac surgery.Patients and methods: This double-blind, randomized, placebo-controlled trial was conducted in patients aged 65 years or older undergoing major elective noncardiac surgery without a planned ICU stay. Eligible patients were randomly assigned to receive either dexmedetomidine (0.1 μg/kg/h) or placebo (0.9% normal saline) immediately after surgery though patient-controlled intravenous analgesia device. The primary outcome was the incidence of delirium during the first 5 postoperative days. Secondary outcomes included postoperative subjective pain scores and subjective sleep quality. The study dates were from January 2018 to January 2019.Results: A total of 557 patients were randomly assigned to receive either dexmedetomidine (n=281) or placebo (n=276). The incidence of postoperative delirium had no difference between the dexmedetomidine and placebo groups (11.7% [33 of 281] vs 13.8% [38 of 276], P=0.47). Compared with placebo group, patients in dexmedetomidine group reported significant lower numerical rating score pain scores at 3, 12, 24, and 48 hrs after surgery (all P<0.05) and significant improved Richards Campbell Sleep Questionnaire results during the first 3 postoperative days (all P<0.0001). Dexmedetomidine-related adverse events were similar between the two groups.Conclusion: Postoperative continuous infusion of dexmedetomidine did not decrease the incidence of postoperative delirium in elderly patients admitted to general surgical wards after elective noncardiac surgery.Keywords: postoperative delirium, dexmedetomidine, elderly patients, pain, sleep